The Relationship between Environmental Concern Attitudes and Elementary School Students' Science Learning Outcomes - Laksana, M. Soeprijadi Djoko; Pangestu, Kasih Septin (LJPI UI Bunga Bangsa Cirebon, 2025)
Objective: This study aims to analyze the relationship between environmental awareness and science learning outcomes of elementary school students in Madiun City. Environmental awareness is an important factor in science education, which is expected to increase students' awareness and understanding of science concepts related to the environment. Novelty: This study highlights the impact of environmental awareness on science learning outcomes, emphasizing its role in enhancing students' understanding and academic achievement, which has not been extensively explored in the context of elementary education in Madiun City. Methods: The research method used is quantitative with a correlational approach. The research sample consisted of elementary school students in several schools in Madiun City who were selected randomly. Data were collected through an environmental awareness questionnaire and a science learning outcome test. Data analysis used the Pearson correlation test to determine the relationship between the two variables. Results: The results showed that there was a positive and significant relationship between environmental awareness and students' science learning outcomes. The higher the students' environmental awareness, the better the science learning outcomes they obtained. Conclusion: This finding indicates that strengthening environmental awareness in science learning can contribute to improving students' understanding and academic achievement.